Colpopexy and urethral suspension with monoprothesis for surgical treatment of cystocele and urinary stress incontinence - Delgado, David (2015)
Objectives: To describe our experience in surgical repair of cystocele and urinary stress incontinence (SUI) using a synthetic monofilament monoprothesis. Design: Retrospective, descriptive, series of cases study. Setting: Gynecology service, Hospital Nacional Cayetano Heredia. Participants: Women who underwent the surgical technique. Interventions: We had 44 patients operated of anterior colpopexy and urethral suspension with monoprothesis mesh (Atrium, Prolene), similar to the NazcaTC mesh, in order to repair cystocele and SUI, between May 2007 and April 2008. Main outcome measures: Cure and complications. Results: By Baden Walter and POP-Q scores, three months after cystocele surgery cure rate was 28/31 (91%) with patient satisfaction in 31/33 (94%). For SUI, cure was found in 27/33 (82%) and improvement in 5/33(15%). The most important complications were urinary tract infection 10/44 (23%), urinary retention 8/44(18%), and vaginal dome infection 4/44 (9%); cystocele recurred in one patient and SUI persisted in another patient. Conclusions: Use of monoprothesis may be safe, effective and with low morbidity to repair both cystocele and SUI; nevertheless it is necessary to follow-up these patients for long term collateral effects or recurrence.